3D-Printed Graphene/Polylactic Acid Electrodes Promise High Sensitivity in Electroanalysis - Manzanares Palenzuela, C Lorena; Novotný, Filip; Krupička, Petr; Sofer, Zdeněk; Pumera, Martin (Analytical chemistry, 2018)
Additive manufacturing provides a unique tool for prototyping structures toward electrochemical sensing, due to its ability to produce highly versatile, tailored-shaped devices in a low-cost and fast way with minimized waste. Here we present 3D-printed graphene electrodes for electrochemical sensing. Ring- and disc-shaped electrodes were 3D-printed with a Fused Deposition Modeling printer and characterized using cyclic voltammetry and scanning electron microscopy. Different redox probes K3Fe(CN)6:K4Fe(CN)6, FeCl3, ascorbic acid, Ru(NH3)6Cl3, and ferrocene monocarboxylic acid) were used to assess the electrochemical performance of these devices. Finally, the electrochemical detection of picric acid and ascorbic acid was carried out as proof-of-concept analytes for sensing applications. Such customizable platforms represent promising alternatives to conventional electrodes for a wide range of sensing applications.